Sams teach yourself JavaScript in 24 hours. - Ballard, Phil; Safari eBooks ([Place of publication not identified] : [Sams], 2015)
"JavaScript Video How-To is a series of short, 2- to 5-minute how-to videos that walk you through a specific task or technique related to creating dynamic, interactive web pages with JavaScript. Adapted from Phil Ballard's book Sams Teach Yourself JavaScript in 24 Hours, each video is self-contained and focused entirely on one particular task. You can either go through the videos in sequence or you can jump into a particular task, see how something is done, and then jump out again."--Resource description page.
Title from resource description page (viewed December 21, 2015).
Presenter, Phil Ballard.
Date of publication and publisher's name from resource description page.
"Video 1.1."
Keywords: JavaScript (Computer program language); Web site development; Electronic books